2019
DOI: 10.1021/acs.analchem.9b03448
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetically Driven Exosome Separation and Concentration Using Dielectrophoretic-Enhanced PDMS-Based Microfluidics

Abstract: Exosomes are a specific subpopulation of extracellular vesicles that have gained interest because of their many potential biomedical applications. However, exosome isolation and characterization are the first steps toward designing novel applications. This work presents a direct current−insulator-based dielectrophoretic (DC-iDEP) approach to simultaneously capture and separate exosomes by size. To do so, a microdevice consisting of a channel with two electrically insulating post sections was designed. Each sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 50 publications
(79 reference statements)
2
74
0
Order By: Relevance
“…Any voltage between 800 and 1000 V increased flow velocity and damaged the device. It was suggested that exosomes trapped by iDEP may be achievable at higher electric potentials [ 110 ]. Following this publication, Sergio et al [ 56 ] in 2019 enhanced the same device and applied 2000 V electric potential difference across the channel length.…”
Section: Discussionmentioning
confidence: 99%
“…Any voltage between 800 and 1000 V increased flow velocity and damaged the device. It was suggested that exosomes trapped by iDEP may be achievable at higher electric potentials [ 110 ]. Following this publication, Sergio et al [ 56 ] in 2019 enhanced the same device and applied 2000 V electric potential difference across the channel length.…”
Section: Discussionmentioning
confidence: 99%
“…utilized a direct‐current insulator based dielectophoretic (DC‐iDEP) method to capture and separate exosomes of different sizes. [ 90 ] By using two electrically insulating post sections driven by iDEP, two subpopulations of exosomes can be successfully separated. For more classified exosome size sorting, Fujiwara et al.…”
Section: Microfluidics‐based Isolation Strategiesmentioning
confidence: 99%
“…[93] More recently, insulator-based DEP (iDEP), a variant of DEP, has gained attention because it does not require the insertion of electrodes in the chip, which can reduce costs and simplify the microfluidic device. [94,95] iDEP is the result of a non-uniform electric field between remote electrodes, implemented by embedding insulating posts in the microchannel. By adjusting the voltage magnitude, the DEP force exerted allows the separation of particles by sizes.…”
Section: Dielectrophoretic Isolation (Dep)mentioning
confidence: 99%
“…For instance, as shown in Figure 8, Ayala-Mar et al presented a direct current-iDEP (DC-iDEP) device with one channel and two electrically insulating posts for exosome isolation. [95] By adjusting the voltage applied across the main channel, larger (≈120 nm) and smaller (≈75 nm) exosomes can be trapped in the first and second parts, respectively. Exosome recovery is also possible in the side channels through electroosmotic flow.…”
Section: Dielectrophoretic Isolation (Dep)mentioning
confidence: 99%